Aberrations in electromagnetic plasma lenses proposed for intense large-aperture ion beam focusing - Butenko, V.I.; Ivanov, B.I. (Вопросы атомной науки и техники, 2003)
It is shown, that in electromagnetic plasma lenses moment aberrations obey the conservation law of the moment of the ion generalized momentum; they disappear when an ion source is placed in a zero magnetic field. Geometrical aberrations can be removed by choice of the optimal electric field intensity distribution along the radius that have been calculated. As a result, the ion current density and beam compression can achieve in the focus a value up to 10³ A/cm², and 10⁵, accordingly. Then influence of discrete distribution of the external (boundary) electrical potential upon ion focusing was studied, and an example of two-lens achromatic system have been investigated as well.